ANALISIS KINERJA SEKOLAH DALAM MEMINGKATKAN MUTU PENDIDIKAN MELALUI AKREDITASI (Studi Pada SMP Sekecamatan Saparua dan Saparua Timur) - Cynthia Lusye Sapulette (Institut Agama Kristen Negeri (IAKN) Ambon, 2019)
his research aims to find out: (1) How does the school prepare to implement school accreditation, which starts with filling in the field of accreditation data